Korea 65 : the forgotten war remembered - Hughes, John C. (John Charles), 1943-; Heffernan, Trova; Larson, Lori (Lori A.) (Office of the Secretary of State, Legacy Washington, 2017)
Korea 65: the Forgotten War Remembered features thirteen personal stories from Washingtonians whose lives were affected by the Korean War.